Profitabilitas, Aktivitas Perusahaan, Tipe Industri dan Pengungkapan Sustainability Report - Wagiswari, Ni Luh Sari; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 31 No 9 (2021)DO - 10.24843/EJA.2021.v31.i09.p13, 2021)
Companies and other business entities must disclose or report the company's social activities included in the sustainability report. However, the level of sustainability report reporting in Indonesia is still low. The purpose of this study was to determine the effect of profitability, company activity, and industry type on the disclosure of sustainability report. This research was conducted at the LQ45 company on the Indonesia Stock Exchange for the period 2017-2019 by accessing the official website ww.idx.co.id. The population in this study amounted to 45 companies. Sampling using purposive sampling technique. The sample in this study were 16 companies with 48 observational data. The analysis technique used in this study was multiple linear regression analysis. Based on the research results, it was found that profitability had a negative effect on the disclosure of sustainability reports. Company activities have a positive effect on sustainability report disclosure. Industry type has no effect on sustainability report disclosure. Keywords: Profitability; Company Activities; Industry Type; Sustainability Report.